The martial rights and duties (Rights and duties of a woman and a man) - هدى عبدالله طاهر (College of Education for Women, 2019)
This research addresses the relevance of men and women and the consequent provisions such as dowry and alimony ... Of the like, marriage is to organize links masculinity and femininity any sexual meeting between men and women a special system that must be produces reproduction him and alone, which gets its reproduction in human kind, and has no family and on the basis of private life is being organized. The importance of the topic see Islam has urged marriage and forbade celibacy, and ensure that the Lord of Glory Almighty married subsidy nor the origin of the differences between men and women in money or workmanship or blue-chip Every Muslim inept any Muslim and every Muslim efficient for any Muslim. The importance of research goes back to the ignorance of women our age and even men also rights marital any ignorance of women, because they must of rights and the consequences for them of the duties so that one of them get married and give birth to and raise and live a long life with her husband and die is ignorant of the most basic rights of a spouse or own rights or the rights of their common , and this is the same what happens to a man, too. It is a reality we live andTouchin society now is the multitude of problems and conflicts that occur between spouses Here are the courts fill the issues of Personal Status, which lead to the disintegration of Alosroziaa for boys and all that stems from ignorance of the people verdicts legitimacy and lack of proper understanding of the relationship between men and women, which can only be done by marriage, according to legal costs it needs in his life is an individual duty for every Muslim because he commanded that does its work in accordance with the provisions legislate. And the importance of conjugal rights and their impact on family formation and rearing children see that Islam may care about this marital relationship and singled out its provisions and processors to disturb the elite of this link, and made interest that bind husband his wife is noted by legislate not mind because Hassan is classed legislate and ugly whatdistortionlegislate and corrupting and interest to be determined legislate. If aware of the husband and wife what is and what Accordingly, the king of the key to peace of mind and tranquility of his life, and those rights governing marital life, and emphasizes the good treatment between spouses, and improves each and every one of them to be given before it takes, and fulfills the rights of partner choice, voluntarily without force, and on the other to This compares charity in truth better than him, Wesera to fulfill the rights of his partner full of spin.